Lecture Review: Research on Media Influence: Shaping Health Behaviors and Social Policy (The Journal of Medicine, Humanity and Media, 2024)
In this lecture, Professor Niederdeppe elucidated the research conducted by his team on the influence of media on shaping health behaviors and social policy. Amidst an increasingly diverse and fragmented landscape of health policy information, the research focused on the dynamics of dissemination in both behavior and policy that influence health and social equity, alongside their consequential effects. By monitoring the environment of public health communications across various issues, the team employed communication theories to examine and implement a range of communicative interventions and innovative methodologies. Initially, the efficacy of public health communication was evaluated based on its ability to meet predetermined objectives, highlighting the multidisciplinary nature of this field. Furthermore, the discourse underscored the critical role of theoretical frameworks and the design of interventions. Utilizing established and empirically validated communication theories can significantly enhance the design and execution of impactful health communication campaigns. Ultimately, health communication is crucial in influencing health policy and practices, advocating for policy-driven initiatives to tackle public health challenges effectively.
Keywords: Health Communication, Policy, Public Health, Behavior Change